ETR 300 Gigapixel / Mohamad Yazid Rashidi… [et al.] - Rashidi, Mohamad Yazid; John, Diana Ubung; Othman, Liyana; Freddie, Trecy; Ali, Mohd Faizall (2010)
In this modern era, it is very common for everyone to start a business. As in Gigapixel, the nature of the business in Gigapixel is in the form of partnership which include the selling of a wide range of products and services. All the persons involved in this business is group of professionals who have come together to collaborate and combined their experiences in Photography and Event industry and formed a company unlike any other. As stated, the nature of the business is in the form of partnership which generally consist-of six shareholder which each of them have contribute a capital for the business as agreed in the agreement. The business is in the form of partnership because we would like to run the business as a team and to achieve equality to each contribution done to the business. We also choose this type of business because the shareholders of the company will always find a way to gain more productivity in terms of profit and benefit to the company. This business plan is prepared by the Gigapixel mainly to obtained working capital loan from Bank Rakyat for the amount of RM23, 659.